The Role of Digital Marketing in the Development of Salt-Based MSMEs: Implementation at the Fajar Samudra Salt Cooperative - Wiwik Handayani (Community Development and Empowerment, 2026)
The development of digital technology has created significant opportunities for Micro, Small, and Medium Enterprises (MSME) to expand market reach and enhance product competitiveness. However, many MSME, including those operating in the salt industry, have not yet fully optimized the potential of digital marketing. Therefore, this article focuses on analyzing the contribution of digital marketing to the development of MSMEs as applied to the Fajar Samudra Salt Farmers’ Cooperative in Blitar Regency. The approach employed in this includes observation, mentoring, and digital marketing training for the partner. The digital marketing strategies implemented consist of establishing social media accounts and marketplace platform, developing promotional content, and providing digital marketing management training for the Cooperative team. The result indicates an improvement in the partner’s understanding of digital marketing strategies and the establishment of sustainable online marketing infrastructure. This program plays a crucial role in preparing Fajar Samudra Salt Cooperative to reach broader markets and support business sustainability in the digital era.